A LITERATURE REVIEW: WOMEN'S ENTREPRENEURSHIP IN THE MODERN ERA - Samuel Morales Simanjuntak; Ritha F. Dalimunthe; Prihatin Lumbanraja (Cahaya Ilmu Bangsa, 2024)
This literature review provides an understanding of the structure of publication-based knowledge about women's entrepreneurship in the modern era. Women entrepreneurs continue to take part in the economy in this era. Women's empowerment is related to women's power in decision making, easy access to information, and control of resources. Women's empowerment plays an important role in economic and social development. Women's entrepreneurial intentions are influenced by cognitive and psychological factors such as creativity, innovation, proactiveness and risk taking. Business ownership by women is widely recognized as an important component of a healthy economy because women play a critical role in creating new jobs and services and contributing to overall economic development. In the business world, men and women have the same rights, without discriminating between each other. Women entrepreneurs have developed their potential and improved the welfare of women who want to start entrepreneurship. Sustainable development in society, business, and, ultimately, countries, among other things, is influenced by important driving forces, such as gender equality. This research uses a literature review method. This review provides a comprehensive knowledge structure based on women's entrepreneurship in the modern era.